2009
DOI: 10.1113/jphysiol.2009.178285
|View full text |Cite
|
Sign up to set email alerts
|

Redox modulation of global phosphatase activity and protein phosphorylation in intact skeletal muscle

Abstract: Skeletal muscles produce transient reactive oxygen species (ROS) in response to intense stimulation, disuse atrophy, heat stress, hypoxia, osmotic stress, stretch and cell receptor activation. The physiological significance is not well understood. Protein phosphatases (PPases) are known to be highly sensitive to oxidants and could contribute to many different signalling responses in muscle. We tested whether broad categories of PPases are inhibited by levels of acute oxidant exposure that do not result in loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 61 publications
(113 reference statements)
2
82
0
2
Order By: Relevance
“…In bloodstream form T. brucei brucei, NEM caused depolarization of the plasma membrane potential, presumably through inhibition of H ϩ -ATPases (41). In addition to ATPases, phosphatases often contain redox-active cysteine residues that are sensitive to oxidation (42). In a related parasite, Trypanosoma rangeli, H 2 O 2 was shown to inhibit the activity of phosphatases in the outer membrane, and thiol-reducing agents reversed phosphatase inhibition (43).…”
Section: Discussionmentioning
confidence: 99%
“…In bloodstream form T. brucei brucei, NEM caused depolarization of the plasma membrane potential, presumably through inhibition of H ϩ -ATPases (41). In addition to ATPases, phosphatases often contain redox-active cysteine residues that are sensitive to oxidation (42). In a related parasite, Trypanosoma rangeli, H 2 O 2 was shown to inhibit the activity of phosphatases in the outer membrane, and thiol-reducing agents reversed phosphatase inhibition (43).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that NOX2 generates ROS in skeletal muscle myotubes in response to insulin (Espinosa et al, 2009). A rise in cellular ROS promotes redox modifications of skeletal muscle proteins (Hidalgo et al, 2004) and a global 'phosphatase tone' (Wright et al, 2009) in both skeletal and cardiac muscle. The thiol (-SH) group of cysteine residues undergoes covalent reactions with oxidants, which produce modifications, such as S-glutathionylation, that give rise to functional alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SHP-1 and SHP-2 activity could be inhibited by oxidative stress generated by ionizing radiation or low H 2 O 2 concentrations in a Ca 2 + -dependent NOS and an S-nitrosylation-dependent manner (9,66,72). Further investigation indicated that oxidative stress-induced inhibition on PTP activity is reversible (46,122,131). ROS accumulation resulting from cytokine treatment decreases the PTP1B activity by oxidative inactivation, which can be restored by the treatment with NAC, an ROS scavenger (46,57).…”
Section: Impaired Tyrosine Phosphatases In Oxidative Stressmentioning
confidence: 93%
“…Excessive generation of ROS has been shown to activate multiple protein kinases, such as extracellular signal-regulated kinase (ERK)1/2, protein kinase B (PKB), and protein tyrosine kinases (PTKs) (25,31,43,50,118,125,127). Additionally, a variety of phosphatases are the sensitive targets of oxidative stress and may be inactivated under oxidizing conditions, which would amplify the effect of redox-linked activation of key protein kinases (60,110,111,131). Given that the balance between protein kinases and phosphatases dictates the overall phosphorylation state of cellular phosphoproteins, aberrant protein phosphorylation may exacerbate the pathophysiology of multiple human diseases and targeting them by small molecules therefore would be anticipated to ameliorate clinical symptoms (34,38,76,79).…”
Section: Introductionmentioning
confidence: 99%